Pemberdayaan UMKM Tradisonal dalam Era Digital : Optimalisasi Tiktok untuk Pemasaraan Krecek - Nur Hanifatur Rohmah; Zaenal Wafa (CV. Aksara Global Akademia, 2025)
Traditional SMEs face significant challenges in surviving the digital era, particularly in product marketing. One proposed solution is utilizing TikTok as a digital platform to expand market reach. This community service activity aims to empower a cassava cracker SME through the implementation of TikTok-based digital marketing strategies. The methods used include initial observation, creative content creation training, technical assistance, and performance evaluation of the TikTok account. The results show an increase in product visibility in the digital market, with significant video views and positive audience responses, including increased product demand. These findings highlight the importance of digital innovation in enhancing the competitiveness of traditional SMEs. In conclusion, empowering SMEs through TikTok can be a strategic step to connect local products with a broader market, promoting business sustainability in the digital transformation era.